Self-aggregation in pyrrole: Matrix isolation, solid state infrared spectroscopy, and DFT study - Gomez Zavaglia, Andrea (2004)
Pyrrole (C4H5N) was embedded in low-temperature solid inert matrixes (argon, xenon; T = 9 K.) and both the monomer and low-order aggregates characterized by FTIR spectroscopy. The spectroscopic studies were complemented by extensive theoretical [DFT(B3LYP)/6-311++G(d,p)] structural and vibrational studies carried out for the monomer and their self-aggregates (up to four units). The calculated spectrum for monomeric pyrrole fits well those obtained immediately after deposition (at 9 K) of diluted matrixes, which can be prepared keeping the compound at low temperature before deposition and using low fluxes of the sublimate. Annealing of the matrixes to higher temperatures or increasing of the gaseous flux during deposition leads to aggregation, which can be easily recognized spectroscopically. On the basis of the theoretically predicted spectra for the monomer, dimer, trimers, and tetramers of pyrrole, assignments were proposed for the experimentally observed bands. It was also found that the formation of the hydrogen-bonded clusters shows a significant cooperativity effect, which was studied in detail and could be related with several structural and spectroscopic parameters. Infrared spectra of the pure solid compound at low temperatures in both amorphous and crystalline states were also studied and interpreted.